Traces: An introduction to the special issue. (May 2016) - Wyatt, Jonathan; Tamas, Sophie; Bondi, Liz
Abstract: This special issue invited scholars from a range of disciplinary and professional backgrounds to engage with the question – writ broad – of what we do with, and how we understand, that which lingers in the shadows. In this introductory paper we begin with some background to this collection, we offer a few over-arching comments concerning the theoretical, aesthetic and practical work we see it as undertaking, and we end with providing a glimpse of the papers.